Keberhasilan Hidup Setek Pucuk Jabon (Anthocephalus Cadamba) Dengan Pemberian Beberapa Konsentrasi Rootone-F - Ferdiansyah Putra; Indriyanto Indriyanto; Melya Riniarti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Kadam (Anthocephalus cadamba) is one types of three possible to develop in plantation forest or public forest to suply log necessity in Indonesia. However, the silviculture information on kadam development is still limited especially in providing nurseries. The objective of this research was to find out survival percentage, shooting ability, and rooting ability of kadam shoot cutting with some concentrations of Rootone-F addmited. This research used completely randomized design with four treatments and five replications. Treatments were soaking the bud of kadam shoot cuttings with some of the following Rootone-F concentrations: 0 ppm, 100 ppm, 200 ppm, and 300 ppm. Variables to observe were survival percentages, shoot lengths, shoot diameters, root lengths, and leaf numbers. The results showed that Rootone-F addmited with 200 ppm concentration resulted in the best shoot height, root length, and leaf numbers of kadam shoot cuttings compared with concentrations of 1 ppm, 100 ppm, and 300 ppm. The kadam shoot cutting with 200 ppm Rootone-F concentration had 96% survival, 20.47 cm shoot length, 19.60 root length, and 6.18 leafs. The conclusion was that the concentration of 200 ppm Rootone-F gives the best results. Keywords: kadam, Rootone-F, shoot cutting